The effects of leadership styles and budget participation on job satisfaction and job performance / Ralph W. Adler and Jonathan Reid - W. Adler, Ralph (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2008)
Previous attempts to study the effects of leadership style and budget participation on job satisfaction and job performance have invariably centered on 1970s conceptions of leadership style. As a consequence, this body of research has failed to capitalise on significant advancements in the conceptualisation and operationalisation of leadership that occurred in the 1980s and 1990s. The present paper incorporates these more modern understandings of leadership, in combination with the traditional conceptions, to examine the effects of leadership style and budgetary participation on employee performance and job satisfaction. In general, only partial support was found for the literature’s existing empirical findings. Moreover, the present study clearly reveals that improved explanation of employee performance and job satisfaction can be attained through the inclusion of the more recent (post 1970s) conceptualisations and operationalisations of leadership. Surprisingly, at least in comparison to earlier studies, the relationships, rather than showing as complex, interactive ones, are apparently of a much simpler, independent nature.